The Role of PD-1 in Acute and Chronic Infection - Jubel, Jil M.; Barbati, Zachary R.; Burger, Christof; Wirtz, Dieter C.; Schildberg, Frank A. (Frontiers in Immunology, 2020)
PD-1 as an immune checkpoint molecule down-regulates T cell activity during immune responses in order to prevent autoimmune tissue damage. In chronic infections or tumors, lasting antigen-exposure leads to permanent PD-1 expression that can limit immune-mediated clearance of patho-gens or degenerated cells. Blocking PD-1 can enhance T cell function; in cancer treatment PD-1 blockade is already used as a successful therapy. However, the role of PD-1 expression and block-ing in the context of acute and chronic infections is less defined. Building on its success in cancer therapy leads to the hypothesis that blocking PD-1 in infectious diseases is also beneficial in acute or chronic infections. This review will focus on the role of PD-1 expression in acute and chronic infections with virus, bacteria and parasites, with a particular focus on recent studies regarding PD-1 blockade in infectious diseases.